2015
DOI: 10.1089/sur.2013.269
|View full text |Cite
|
Sign up to set email alerts
|

Endogenous Interleukin 18 Suppresses Hyperglycemia and Hyperinsulinemia during the Acute Phase of Endotoxemia in Mice

Abstract: Background: Hyperglycemia associated with insulin resistance is common among critically ill patients. Interleukin (IL)-18 has been linked with hyperglycemia and insulin resistance in chronic disease, but the relation between IL-18 and insulin resistance during critical illness was unexplored. This study investigated whether IL-18 modulates hyperglycemia and insulin resistance during acute inflammation. Methods: We injected lipopolysaccharide (LPS) 40 mg/kg into wild-type (WT) and IL-18 knockout (KO) mice to in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
5
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 28 publications
2
5
0
Order By: Relevance
“…Moreover, similar associations were found in studies on the impact of postprandial hyperglycemia and hypertriglyceridemia on endothelial inflammation [45][46][47]. IL-18 may attenuate lipid metabolism, postprandial hyperglycemia, and modulate insulin signalling [45] and by triggering endothelial inflammation, promote the formation of atherosclerotic plaques [45][46][47].…”
Section: Discussionsupporting
confidence: 70%
“…Moreover, similar associations were found in studies on the impact of postprandial hyperglycemia and hypertriglyceridemia on endothelial inflammation [45][46][47]. IL-18 may attenuate lipid metabolism, postprandial hyperglycemia, and modulate insulin signalling [45] and by triggering endothelial inflammation, promote the formation of atherosclerotic plaques [45][46][47].…”
Section: Discussionsupporting
confidence: 70%
“…Additionally, septic patients suffering acute respiratory distress syndrome (ARDS) had higher plasma IL-18 levels than septic patients without ARDS (13). In our previous report, which was the first report focusing on IL-18 and transient insulin resistance mediated by acute inflammation, we found that endogenous IL-18 attenuated transient hyperglycemia by enhancing hepatic insulin signaling during the hyperacute phase of lipopolysaccharide (LPS)-induced lethal endotoxemia (14).…”
Section: Il-18 Is a Pro-inflammatory Cytokine Secreted By T-cells Mamentioning
confidence: 96%
“…Western blotting was performed as described previously (14). was determined in a previous study (17).…”
Section: Blood Analysismentioning
confidence: 99%
“…Moreover, there is a relationship between hyperglycemia and altered cellular metabolism in critically ill patients that results in insulin resistance and release of systemic in ammatory mediators [6]. Earlier studies suggested that proin ammatory cytokines such as interleukin (IL)-6 and IL-18 are involved in glucose metabolism and insulin action; therefore, hypercytokinemia may have a potential role in increased glucose levels [6,12,13]. This indicates that immunoneuroendocrine alterations might be involved in the pathophysiology of SIH during acute illnesses [14].…”
Section: Introductionmentioning
confidence: 99%